The price of robustness; impact of worst-case optimization on organ-at-risk dose and complication probability in intensity-modulated proton therapy for oropharyngeal cancer patients. Issue 1 (July 2016) - van de Water, Steven; van Dam, Iris; Schaart, Dennis R.; Al-Mamgani, Abrahim; Heijmen, Ben J.M.; Hoogeman, Mischa S.
Abstract: Purpose: To quantify the impact of the degree of robustness against setup errors and range errors on organ-at-risk (OAR) dose and normal tissue complication probabilities (NTCPs) in intensity-modulated proton therapy for oropharyngeal cancer patients. Material and methods: For 20 oropharyngeal cases (10 unilateral and 10 bilateral), robust treatment plans were generated using 'minimax' worst-case optimization. We varied the robustness against setup errors ('setup robustness') from 1 to 7 mm and the robustness against range errors ('range robustness') from 1% to 7% (+1 mm). We evaluated OAR doses and NTCP-values for xerostomia, dysphagia and larynx edema. Results: Varying the degree of setup robustness was found to have a considerably larger impact than varying the range robustness. Increasing setup robustness from 1 mm to 3, 5, and 7 mm resulted in average NTCP-values to increase by 1.9, 4.4 and 7.5 percentage point, whereas they increased by only 0.4, 0.8 and 1.2 percentage point when increasing range robustness from 1% to 3%, 5% and 7%. The degree of setup robustness was observed to have a clinically significant impact in bilateral cases in particular. Conclusions: For oropharyngeal cancer patients, minimizing setup errors should be given a higher priority than minimizing range errors.